Cohabitation, marriage, relationship stability and child outcomes: Final report - Claire Crawford; Alissa Goodman; Ellen Greaves (Institute for Fiscal Studies (IFS), 2013)
This report considers the extent to which differences in parental characteristics explain gaps in cognitive and socio-emotional development between children at older ages. It documents and explores the differences between children born to cohabiting and married couples for a range of other non-cognitve skills such as engagement in risky behaviours. It draws together and extends work showing the differences in relationship stability between cohabiting and married couples, and the extent to which these differences may play a role in explaining the gaps in cognitive and socio-emotional development between children born and raised in different family forms.
Keywords: 330